Weight of diagnostic characteristics in the assess ment of tourism potential of rural areas according to Siedlce inhabitants (Geography and Tourism, 2021)
The presented work is an attempt to determine the importance of individual diagnostic characteristics conditioning rural tourism development by calculating their weights. The research was conducted in 2020 and involved the inhabitants of the city of Siedlce. The research method comprised a diagnostic survey. The authors’ research tool of choice was a questionnaire. The research pertained to an assessment of characteristics reflecting the tourism potential of rural areas in Poland. Evaluation of attitudes was based on a 10-grade Likert scale. The resulting point scores were used to calculate weights of characteristics affecting tourism development in rural areas. The characteristics representing structural resources which had the greatest impact on rural tourism development included: presence of natural water bodies in the commune, number of historic sites,number of food and beverage serving establishments, convenient road access to the commune’s administrative centre, and distance between the locality and the nearest town whose population exceeds 20 thousand inhabitants. Considering functional resources, indicators which may enhance an area’s attractiveness to tourists include commune’s ability to obtain EU funds and their expenses on tourism and entrepreneurship.